A likely runaway star cluster in the outer disc of the Large Magellanic Cloud - Piatti, Andrés E.; Salinas, Ricardo; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present results from photometric and spectroscopic data obtained with SOAR and Gemini observatory facilities in the field of a recently discovered